KONTRIBUSI LIKUIDITAS DAN LEVERAGE TERHADAP HARGA SAHAM DAN PROFITABILITAS PERUSAHAAN MANUFAKTUR - Dwi Susilowati; Suhartono; Juwari; Melda Yulinda; Wiwik Saraswati (KRISNA: Kumpulan Riset Akuntansi, 2026)
Liquidity contribution is measured by fast ratio and current ratio while Leverage is measured by two indicators Debt  to Asset Ratio and Debt  to Equity  Ratio at stock of prices by mediation using Profitability which is measured using  the Return on Asset Ratio and Return on Equity Ratio indicators. Data is taken from financial position reports and annual reports. Observations used 6 manufacturing entities indexed LQ45 manufacturing l of 24 observations. This study of uses method regression analysis tools with a quantitative result  using SmartPLS 4.  From this study, it is said that liquidity has no effect on probability but liquidity has an effect on stock prices and profitability is not able to mediate the relationship between liquidity and stock prices. While the average has no effect on the stock price, neither can profitability mediate the relationship between leverage and the stock price.